Study on Level of Knowledge on Climate Change Among the People Residing in a Selected Area of Dhaka City - Hossain, Sarder Mahmud; Sheikh, Md. Alif; Tarafdar, Monowar Ahmad; Baroi, Supti (Anwer Khan Modern Medical College Journal, 2013)
A descriptive type of cross sectional study was conducted at Badda, Dhaka to assess the level of knowledge on climate change of the people with a purposive sample size of 226. Nearly half of the respondents heard about the global warming but 43.24% didn't. A major portion of the respondents (62.39%) agreed to include the Climate Change in school curriculum. 39.38% respondents strongly agreed that the world climate is changing but it was due to human behavior which was strongly agreed by 16.81%. 17.26% strongly believed that developed countries are the main contributors. 15.49% of the respondents strongly agreed that developed countries should provide compensation to the affected developing countries. Neither agreed nor disagreed that the Climate Change had impact on economy was 38.06% but 40.27% respondents strongly agreed that Climate has impact on human health. 36.73% respondents strongly agreed that Climate Change has impact on food production and 34.07% strongly agreed that it has impact on soil condition and fertility. 49.56% respondents strongly agreed for the need to take measure to reduce or prevent Climatic Change and 43.23% strongly agreed on awareness creation to cope with Climate Change. TV/RADIO was the most important source of information about global warming (82.75%). The association between educational level and knowledge on Climate Change was found to be significant. As the climate change has already put a devastating impact on survival on millions, effective action plan to be undertaken to control the impact on environment and create awareness about the adverse effects of it on the globe. Anwer Khan Modern Medical College Journal Vol. 4, No. 2: July 2013, Pages 5-9 DOI: http://dx.doi.org/10.3329/akmmcj.v4i2.16916